DETERMINAN FINANCIAL BEHAVIOUR DENGAN DIMODERASI GENDER PADA GEN Z - Mauliddah, Nurullaili; Sari, Tyasha Ayu Melynda; Pradina, Sherly Budi; Yushartono, Irmanafia Putra (Universitas Nusa Cendana, 2024)
Gen Z has more expressive characteristics and tends to be tolerant and multitasking. According to the Research Institute in 2019, the allocation of savings from income was only 10.17% for both men and women in Generation Z. This research aims to analyze the moderating influence of gender in predicting financial behavior, which is influenced by self-efficacy, financial literacy, and locus of control in Gen Z by using path analysis with moderation assisted by SmartPLS software. This research shows that self-efficacy, financial literacy, and locus of control significantly affect economic behavior. However, gender cannot moderate the influence of these variables on FEB UM Surabaya students. Keywords: Financial Behaviour; Self Efficacy; Financial Literacy; Gender